Combined efects of tree size and tapping techniques on resin production of Boswellia dalzielii Hutch., an African frankincense tree - SABO, Prospère; Salako, Kolawolé Valère; Glèlè kakaï, Romain; OUÉDRAOGO, Amadé (My University, 2022)
Boswellia dalzielii Hutch. is an African frankincense tree species with high medicinal and economic values mostly derived from its resin. In Burkina Faso, it has potentials to be the source of signifcant income for local communities, but it is currently neglected and underutilized. This study aims to assess the species resin production in relationship to tree size, tapping technique, season, intensity, and frequency of harvesting in natural stands of Sudano-Sahelian zone of Burkina Faso. Two independent experiments were conducted on resin yield: (i) experiment 1 combined the tapping technique (six techniques) and tree stem-diameter (10–20 vs. 20–30 cm) using 120 trees; (ii) experiment 2 used the slant incisure tapping technique (best from the frst experiment) and combined fve tapping intensities (number of grooves: 2, 4, 6, 8 and 10), period of tapping (cold vs. hot dry season), and tree stem-diameter (10–20, 20–30, and>30 cm), using 90 trees. For each experiment, resin production was collected every 2 weeks for 12 weeks. Analysis of variance and linear mixed model on longitudinal data were used for data analyses. All trees had exudated resin and the average resin yield per tree was 36.28±8.62 g (experiment 1) and 40.43±3.82 g (experiment 2). Tapping techniques and intensity, and tree stem-diameter had signifcant (P <0.001) efect on resin yield. Slant incisure tapping yielded the highest resin production, followed by tapping in E-shape cut, V-shape cut and circular tape (intermediate yield production), whereas thin deep vertical incisure and node tape gave the lowest resin production. Larger trees exuded higher quantity of resin. Higher tapping intensity and frequency (wound renewal) also gave higher resin production. Trees tapped during hot dry season produced 1.23 times higher quantity of resin (44.58±7.51 g) than in cold dry season. The fndings of this research could help design better harvesting strategies for the sustainable management of B. dalzielii resources in West Africa
Keywords: Non-wood forest products · Tapping techniques · Seasonality · Yield · Burkina Faso